Penyimpangan Pelaksanaan Pemilihan Umum Tahun 2024 - Kuswan Hadji; Naura Nurul Fajri; Aulia Nur Azizah; Suci Wulandari; Rita Fitri Utami; Fani Rahmasari (Jurnal Hukum dan Sosial Politik, 2024)
General elections or elections that occur in Indonesia are held regularly every 5 years, in which the general election is held in 2024, in general elections the people give their aspirations to vote to elect members of the executive and legislative members, so that members of the legislative and executive candidates register themselves with the General Election Commission (KPU) thus prospective legislative and executive members must follow the regulations issued by the KPU. Through the normative juridical research method, the approach is very relevant in examining campaign implementation deviations from the perspective of administrative law and criminal law. The practice of legislative elections still has deviations from the law by legislative and executive candidates thus the consequences obtained by the candidates and also the role of Bawaslu must be for the affirmation of deviations in the 2024 general election.